The Role Of Literacy In Managing Financial Technology - Arifiani, Rahmawaty (Yayasan Pendidikan Belajar Berdikari, 2024)
The purpose of this study is to examine how financial management practices, through their mediation by financial literacy and financial technology (fintech), affect business performance. This study employs a quantitative research design with Sobel tests for mediation testing and covariance-based partial least squares (PLS) testing techniques. Users of